Requirement Engineering for Knowledge-Intensive Processes: Reference Architecture for the Selection of a Learning Management System - Wundenberg, Sven-Michael (Springer, 2016)
Sven-Michael Wundenberg discusses the development of a reference architecture for the Learning Management System’s (LMS) selection-process aimed at the system’s implementation in a polytechnic-knowledge-transfer organization. The focus lies on the requirement engineering (RE) process’s quintessence based on research about standard RE-procedures and -approaches combined with LMS-basic knowledge and LMS-best-practice experiences. The resulting reference-